Peripheral vascular lesions with the development of hand and foot skin necrosis in a patient with COVID-19: a case report - E. A. Shikina; A. B. Zemlyanoy; E. A. Kazubova; T. V. Urzhumova; N. P. Krylova; G. G. Arabidze (Российский кардиологический журнал, 2022)
In the presented case report, 36-year-old female patient, who was hospitalized in the rheumatology department, developed thrombotic microangiopathy and sepsis-related coronavirus disease 2019 (COVID-19). In the department, hereditary thrombophilia was revealed: heterozygous polymorphism in the coagulation factor 5 gene (Factor V Leiden). Livedo reticularis. It is known that in October 2020, the patient had COVID-19 with bilateral pneumonitis on chest computed tomography. On examination, dry gangrene of 1, 2, 4, 5 fingers of the right hand, 2 finger of the left hand, as well as 2, 3, 4, 5 fingers of the right and left feet were diagnosed. Necrosis of the nasal tip. Surgery was performed with amputation of the affected fingers and distal feet with autodermoplasty.